A Look at Language Learning Strategies of Indonesian High School Students as Foreign Language Learners - Hasanah, Putri; Wiedarti, Pangesti (FKIP Universitas Lampung, 2021)
A look at Language Learning Strategies of Indonesian High School Students as Foreign Language Learners. Objective: This study analyzed Indonesian high school student’s choice of language learning strategies as EFL users, predominantly determining the most frequently used strategies. By understanding learning strategies, it can help EFL students to accelerate their language learning. Methods: One hundred and forty Darul Hasan high school students of Padangsidimpuan participated in this survey. All grades from 2020/2021 participated in this survey study. The Oxford’s strategy inventory for language learning (SILL) translated version was implemented to decide their learning strategies. Findings: The result showed that the students are medium strategy users. The affective strategy was found to be the most dominant strategy used by the students. The students do not seem aware that learning strategies were a part of their learning process. Conclusion: The students and teachers need to improve the learning language strategy for a better learning process.Keywords: language learning strategy, Oxford’s strategy inventory for language learning, survey method. DOI: 10.23960/jpp.v11.i2.202114